1981
DOI: 10.1088/0034-4885/44/11/002
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of surfaces in space

Abstract: In the last decade, large electrostatic potentials of the order of tens of kV have been measured on spacecraft in the Earth's magnetosphere. Observations in space have led to the inference of large potentials on natural objects in the solar system. The result for spacecraft can be material damage and operational interference caused by electrostatic discharges. Natural objects such as dust grains can be disrupted, and their motion influenced by electromagnetic forces. The potential of a body in space is determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
556
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 961 publications
(572 citation statements)
references
References 237 publications
11
556
0
Order By: Relevance
“…In general, the electron thermal velocity u t,e is much larger than u ∞ and the electron distribution can be described by the Boltzmann factor [57]. As a result, the electron current (I e ) from random particle flux per unit surface area to a surface with potential φ B is [57],…”
Section: Charging Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the electron thermal velocity u t,e is much larger than u ∞ and the electron distribution can be described by the Boltzmann factor [57]. As a result, the electron current (I e ) from random particle flux per unit surface area to a surface with potential φ B is [57],…”
Section: Charging Theorymentioning
confidence: 99%
“…Brundin [14]'s conclusions were based on the assertion that LEO spacecraft surface potentials never became more negative than −0.75 V, a statement supported by major works of the era [ 25,56,57]. The growing sophistication of spacecraft, particularly in LEO, has lead to an increased interest in the interaction of highly charged space platforms with the LEO environment [26,29] (see [53,54] for example).…”
Section: Introductionmentioning
confidence: 99%
“…Lunar Prospector data have shown that electrons are reflected not only by magnetic fields but also by electric fields. In shadow, where we make most of our measurements, the lunar surface tends to charge up to ~40 V negative because of the difference in thermal flux from electrons and ions (see Whipple [1981] for a review of the physics behind surface charging, and Knott [1973] and Horanyi et al…”
Section: Lunar Prospector Electron Reflectometry Datamentioning
confidence: 99%
“…[45] For a spacecraft in the geosynchronous environment it is often a good approximation to describe the collection of charged particles by using the orbit-limited Langmuir probe formula [Garrett, 1981;Whipple, 1981]. Consider an electron traveling at velocity V from infinite distance (r = 1) toward a spherical spacecraft that has an attractive potential f(>0).…”
Section: Discussionmentioning
confidence: 99%